2006
DOI: 10.1002/jsfa.2635
|View full text |Cite
|
Sign up to set email alerts
|

Leaching of aluminium from utensils during cooking of food

Abstract: The use of aluminium utensils for cooking provides an important route for aluminium metal to enter foods. Leaching of aluminium from utensils made of aluminium, indalium (alloy of aluminium), stainless steel and hard anodised aluminium was studied under different conditions of pH and boiling time. Low pH was found to enhance leaching of aluminium from the utensils. The leaching was found to be the highest during first-time preparation (new utensils) of all the foods as compared with second-and third-time prepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
27
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 15 publications
5
27
0
1
Order By: Relevance
“…High acidity products such as cheese and yoghurt resulted in greater leaching of aluminium into the food from the utensils. Similar observation has also been reported by Semwal et al (2006). It was also observed that curdling gives rise to increased concentrations of aluminium in the curd and end product compared to raw milk.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…High acidity products such as cheese and yoghurt resulted in greater leaching of aluminium into the food from the utensils. Similar observation has also been reported by Semwal et al (2006). It was also observed that curdling gives rise to increased concentrations of aluminium in the curd and end product compared to raw milk.…”
Section: Resultssupporting
confidence: 89%
“…One of the potential sources of additional dietary aluminium is the aluminium utensils (Semwal et al, 2006). The concentrations of aluminium in milk and milk products after processing in aluminium and stainless steel utensils are presented in Table 3.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite being harmless in lower concentrations, high Al intake results in chronic health effects in long run ( Semwal et al, 2006). Use of aluminum utensils for cooking is reported to cause Al ingestion ( Semwal et al, 2006). Major sources of dietary intake include synthetically added aluminum (i.e.…”
Section: Introductionmentioning
confidence: 99%